N ‐phase logistic chaotic sequence and its application for image encryption. Issue 9 (1st December 2016) - Liu, Lingfeng; Miao, Suoxia; Hu, Hanping; Cheng, Mengfan
Abstract : In this study, the authors use a non‐symmetric partition to generate N ‐phase pseudorandom sequences using the logistic maps. The theoretical analysis shows that this N ‐phase logistic sequence is with uniform distribution, as well as independent and identically distributed. Numerical experiments show that these N ‐phase logistic sequences have high complexity and are with good randomness. A fast algorithm with its time complexity be O ( M ) is proposed to generate these N ‐phase sequences. Furthermore, they propose a new image encryption algorithm based on the N ‐phase logistic sequence, which is combined with both shuffling and substitution algorithms. Several security tests are carried out to demonstrate that the authors' new algorithm is with a high security level, and can resist various attacks, which can be competitive with some other recently proposed image encryption algorithms.